Comparison of different extraction solvent mixtures for characterization of phenolic compounds in strawberries - Kajdzanoska, Marina; Petreska, Jasmina; Stefova, Marina (My University, 2011)
Eight different solvent mixtures containing acetone or methanol pure or combined with an acid (acetic, formic, hydrochloric) were tested for their efficiency for extraction of phenolic compounds from strawberries belonging to five groups of polyphenols: anthocyanins, flavonols, flavan-3-ols, hydroxycinnamic acid derivatives and conjugated forms of ellagic acid. Twenty-eight compounds from these five groups have been detected and quantified using HPLC-DAD-ESI-MS(n). The yield of each phenolic compound and group was evaluated with regard to the extraction solvent composition. Acetone containing extraction mixtures were superior to the ones containing methanol for extraction yield of total phenolic compounds, which was especially pronounced for the groups of flavan-3-ols and conjugated forms of ellagic acid. The mixture acetone/acetic acid (99:1, v/v) gave the best results for the qualitative and quantitative assay of the polyphenols present in strawberries since all 28 compounds were detected only in these extracts in quantities higher or comparable to the other extraction solvents tested.